Discovery of ONO-8590580: A novel, potent and selective GABAA α5 negative allosteric modulator for the treatment of cognitive disorders. Issue 22 (15th November 2020) - Lewis, A.; Beresford, A.; Chambers, M.S.; Clark, G.; Hartley, D.C.; Hirst, K.L.; Higashino, M.; Kawahadara, S.; Nakanishi, M.; Saito, T.; Imagawa, A.; Habashita, H.; et al.
Graphical abstract: Abstract: The identification and SAR development of a series of negative allosteric modulators of the GABAA α5 receptor is described. This novel series of compounds was optimised to provide analogues with high GABAA α5 binding affinity, high α5 negative allosteric modulatory activity, good functional subtype selectivity and low microsomal turnover, culminating in identification of ONO-8590580 .